Analisis Perkembangan Lembaga Keuangan Mikro Syariah (LKMS) di Indonesia - aan Nasrullah (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2020)
This study aims to analyze the development of MFIs (Islamic microfinance institutions) as sharia financial institutions that have a role and focus on improving public Islamic financial literacy. The development of the MFIs can be analyzed based on the development of the MFIs institutions and products. MFIs operating in Indonesia have various types and forms based on the initiator of the establishment of the MFI and its market segmentation. The initiator of the establishment of the MFI can be divided into two, namely, non-government (private) and government. MFIs established by the private sector are cooperatives, banks, custom-based MFIs, and educational institution-based MFIs. Meanwhile, MFIs established by the government can be divided into MFIs established by the Central Government, BUMN (State-Owned Enterprises) and Regional Governments. In terms of contracts and products, the product dynamics in MFIs activities look very high and more varied. For example, distribution of funds is used in almost all Islamic financial institutions, but each institution has its own characteristics in choosing products and funding contracts. In general, fund lending products currently used by both the international and national financial industries use two contract bases, namely the profit sharing and buying and selling contracts.